Long‐Term Imaging: Supported Lipid Bilayers on Fluorescent Nanodiamonds: A Structurally Defined and Versatile Coating for Bioapplications (Adv. Funct. Mater. 45/2018). (5th November 2018) - Vavra, Jan; Rehor, Ivan; Rendler, Torsten; Jani, Mona; Bednar, Jan; Baksh, Michael M.; Zappe, Andrea; Wrachtrup, Joerg; Cigler, Petr
Abstract : Fluorescent nanodiamonds (FNDs) with nitrogen‐vacancy centers enable optical readout of local changes in electric and magnetic fields. In article1803406, Petr Cigler and co‐workers report biomimetic architectures on FNDs based on supported lipid bilayers. They function as "molecular modular bricks", tailoring the interface of particles for specific applications and transducing the changes in local environment to nitrogen‐vacancy centers with remarkable sensitivity.